Quantifying meso‐mammal cave use in central Texas. Issue 1 (14th December 2017) - Montalvo, Andrea E.; Lopez, Roel R.; Parker, Israel D.; Silvy, Nova J.; Cooper, Susan M.; Feagin, Rusty A.
Abstract : Knowledge of meso‐mammal cave use is essential for natural resource managers, particularly in the management of endangered cave invertebrates. Scat left by meso‐mammals represents significant nutrient inputs into the oligotrophic cave environment which can disrupt the invertebrate species composition and ecology. Since little is known about what constitutes typical timing or frequency of meso‐mammal visitation, current management practices are largely speculative. Central Texas caves were historically associated with raccoons Procyon lotor, but with the loss of large predators and encroachment of woody vegetation, the now naturalized North American porcupine Erethizon dorsatum has become an established part of the local ecosystems whose effect on cave biology remains unknown. Our objective with this study was to quantify meso‐mammal cave use according to seasons, time of day, weather conditions, as well ecological and physical cave characteristics. We monitored 30 caves by placing trail cameras at cave entrances for one year on Joint Base San Antonio‐Camp Bullis military base just north of San Antonio, Texas. North American porcupines, raccoons, and Virginia opossums Didelphis virginiana were the three most commonly photographed meso‐mammals (>87%). All meso‐mammal groups showed significantly different cave use according to season, weather, and cave characteristics. Data suggested most meso‐mammals were using caves for denning while raccoons and Virginia opossums also were feeding on resident invertebrate and rodent populations. In particular, Virginia opossum and raccoon, both potential predators of endangered species, showed greater use of caves containing endangered species. The results from our study represent an initial step in understanding meso‐mammal cave use in central Texas.